The need for speed: escape velocity and dynamical mass measurements of the Andromeda galaxy. Issue 3 (10th January 2018) - Kafle, Prajwal R; Sharma, Sanjib; Lewis, Geraint F; Robotham, Aaron S G; Driver, Simon P
Abstract: Our nearest large cosmological neighbour, the Andromeda galaxy (M31), is a dynamical system, and an accurate measurement of its total mass is central to our understanding of its assembly history, the life-cycles of its satellite galaxies, and its role in shaping the Local Group environment. Here, we apply a novel approach to determine the dynamical mass of M31 using high-velocity Planetary Nebulae, establishing a hierarchical Bayesian model united with a scheme to capture potential outliers and marginalize over tracers unknown distances. With this, we derive the escape velocity run of M31 as a function of galactocentric distance, with both parametric and non-parametric approaches. We determine the escape velocity of M31 to be 470 ± 40 km s −1 at a galactocentric distance of 15 kpc, and also, derive the total potential of M31, estimating the virial mass and radius of the galaxy to be 0.8 ± 0.1 × 10 12 M⊙ and 240 ± 10 kpc, respectively. Our M31 mass is on the low side of the measured range, this supports the lower expected mass of the M31–Milky Way system from the timing and momentum arguments, satisfying the H i constraint on circular velocity between 10 ≲ R / kpc < 35, and agreeing with the stellar mass Tully–Fisher relation. To place these results in a broader context, we compare them to the key predictions of the ΛCDM cosmological paradigm, including the stellar-mass–halo-mass and the dark matter halo concentration–virial mass correlation, and finding it to be an outlier to this relation.